STRATEGI DAN TANTANGAN PENGUMPULAN DANA HASIL KOIN NU PADA UPZIS NU KECAMATAN BATANGHARI LAMPUNG TIMUR - Ansori Yahya; Khoirul Abror; Erike Anggraeni (EKSYA : Jurnal Ekonomi Syariah, 2022)
The Zakat Infaq and Shodaqoh Nahdlatul Ulama Management Unit (UPZIS NU) of Kecamatan Batanghari has formed several NU UPZIS at the village or sub-district level. The program currently being carried out by the Infaq Zakat Management Unit and Shodaqoh Nahdlatul Ulama at the village level is the "Nahdlatul Ulama Infaq Box Movement" (KOIN NU). However, in its implementation there are several obstacles experienced by several UPZIS NU at the village level in Kecamatan Batanghari. Some of these obstacles include the distribution of Infaq Boxes to the community that has not been maximized, there are still pros and cons and even rejection in the community regarding the implementation of activities. The purpose of this study was to find out what caused the NU KOIN Program to not be maximized as well as the pros and cons and even rejection in the community about the implementation of activities in several villages in Kecamatan Batanghari. This research was conducted using a qualitative descriptive method, namely research that utilized qualitative data and then described it descriptively. Data collection in this study was carried out using primary data and secondary data. The result of this research is that the response of the people of Batanghari Sub-district to the KOIN NU program is very good. However, due to the lack of socialization, the vastness of the area and the absence of a special team tasked with socializing activities in the community, the implementation of activities in the community has not been maximized and there are still pros and cons and even rejection in the community. The solutions offered by researchers related to this problem are First, UPZIS NU Management at all levels must be more aggressive in conducting socialization in the community, including forming a special team to conduct socialization directly or through social media; Second, the results of the infaq box must be immediately distributed to the community; Third, always coordinate with religious leaders and community leaders; Fourth, submit reports related to the management of KOIN NU results to the community for the sake of transparency.